“Monitoreo de la deforestación en las provincias de moyobamba y rioja de la región de San Martín” - Ysuiza Pérez, Alfredo (2004)
Taking into account that the forests are one of the most voluble ecosystem of the World but the man, in his desire to improve his life conditions, carries out the activities bringing inevitable damage to this natural recourse with the famous problem of deforest. In this case, the present investigation work is denominated as "Monitor of Deforest in Moyobamba and Rioja Province in San Martin Region", with the purpose of relying on the base instrument to help in making proposals of supported development, compatible with natural and actual characteristics of the mentioned above provinces. lt's necessary to indicate that the analysis of the images of satellite Lansat 5 (TM 1986 year) and Landsat 7 (ETM + 1 999 year) were made first at the study, the same made first at the study, the same satellites were processed spending the Systems of Remote Perception and the Systems of Geographical lnformation, using Software's ERDAS IMAGINE, ARCJINFO and ARCVIEW, furthermore extension file of DBF which is compatible with FOXPRO. In Moyobamba Province, there is a deforest increase cf 3 065.25 ha per year . which represents deforest rate of 1.105%, if we continued to use this, it will forecast that ali vegetal area will be consumed in 54 years. In Rioja Province, deforest rate of 0.75%, depends on reaming these events, it's projected that all forest area will be consumad in 70 years.